Pemanfaatan Tanah Kosong untuk tanaman pangan Di Kabupaten Bantul= Utilization of Unused Land for Growing Crops in The District of Bantul - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT Article 6 of UUPA (Basic Agrarian Law) states that "all land rights have a social function". This article signifies that holders of land rights are not allowed to let their land in an idle state, or unused. In reality there are still many individuals, legal entitities, and government agencies that do not utilize the land they occupy. In response to the country's current crisis, which has resulted in the problem of food supply for the majority of the population, the government has adopted a policy in the form of Regulation of the State Minister for Agrarian Affairs/Head of the National Land Agency No. 3 of 1998 concerning the Obligation to Utilize Unused Land for Growing Crops. This research was conducted to find out the contributing factors to the existence of idle land, the procedures followed by other parties for the utilization of idle land growing crops, and legal protections for landholders and those who utilized land. This is a descriptive research as it seeks to describe and to solve the problem. The research was carried out in the District of Bantul, which is one of the disctricts where the AMP program (involvement of the Armed Forces in helping rural communities in the field of agriculture) is implemented. Respondents consisted of 60 landowners and 60 farm-workers as well as 7 developers who owned unused land in Bantul. To complete the data, 9 resource persons were interviewed. The data were then analyzed qualitatively and the statistical data were tabulated to facilitate the analysis. The research reveals the following findings: (1) The developers' land are unused because there are no requests from the community for housing development, which is caused by their economic conditions. From the point of fiew of the community, the contributing factors economic conditions, lack of time and labour, the fact that the owners live in other places, and because they still have no plants to utilize their lands. (2) In general the developers do not comply with the stipulations in PMNA/KBPN No. 3 of 1998. In the case of developers whose lands are utilized by other parties (i.e. former landowners), arrangements are made orally. In the case of the private lands in which are utilized by AMP, the